Exploring the Mechanism of Danshensu in the Treatment of Doxorubicin-Induced Cardiotoxicity Based on Network Pharmacology and Experimental Evaluation - Qi, Jia-ying; Yang, Ya-kun; Jiang, Chuan; Zhao, Yang; Wu, Yong-chao; Han, Xue; Jing, Xuan; Wu, Zhong-lin; Chu, Li (Frontiers in Cardiovascular Medicine, 2022)
Background: Doxorubicin (DOX) is one of the most effective chemotherapeutic agents available; however, its use is limited by the risk of serious cardiotoxicity. Danshensu (DSS), an active ingredient in Salvia miltiorrhiza, has multiple cardioprotective effects, but the effect of DSS on DOX-induced cardiotoxicity has not been reported. Objectives: Predicting the targets of DOX-induced cardiotoxicity and validating the protective effects and mechanisms of DSS. Methods: 1) Using methods based on network pharmacology, DOX-induced cardiotoxicity was analyzed by data analysis, target prediction, PPI network construction and GO analysis. 2) The cardiotoxicity model was established by continuous intraperitoneal injection of 15 mg/kg of DOX into mice for 4 days and the protective effects and mechanism were evaluated by treatment with DSS. Results: The network pharmacology results indicate that CAT, SOD, GPX1, IL-6, TNF, BAX, BCL-2, and CASP3 play an important role in this process, and Keap1 is the main target of DOX-induced cardiac oxidative stress. Then, based on the relationship between Keap1 and Nrf2, the Keap1-Nrf2/NQO1 pathway was confirmed by animal experiments. In the animal experiments, by testing the above indicators, we found that DSS effectively reduced oxidative stress, inflammation, and apoptosis in the damaged heart, and significantly alleviated the prolonged QTc interval caused by DOX. Moreover, compared with the DOX group, DSS elevated Keap1 content and inhibited Nrf2, HO-1, and NQO1. Conclusion: The results of network pharmacology studies indicated that Keap1-Nrf2/NQO1 is an important pathway leading to DOX-induced cardiotoxicity, and the results of animal experiments showed that DSS could effectively exert anti-oxidative stress, anti-inflammatory and anti-apoptotic therapeutic effects on DOX-induced cardiotoxicity by regulating the expression of Keap1-Nrf2/NQO1.